The Effect of Using Blooket Games on Students’ Vocabulary Mastery at SMP Negeri 5 Kota Bengkulu - Alfaiza, Lolla; Susanto, Ferri; Revola, Yashori (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the effect of using Blooket Games on the vocabulary mastery of eighth-grade students at SMP Negeri 5 Kota Bengkulu. The background of this research is based on students’ low vocabulary mastery caused by the use of conventional teaching methods, limited variation of learning media, and low student motivation in learning English vocabulary. This study employed a quasi-experimental method using a Non-Equivalent Control Group Design, involving two classes as the experimental group and the control group. The research instrument used was a vocabulary test in the form of pre-test and post-test to measure students’ vocabulary mastery before and after the treatment. The findings of the study revealed that there was a significant improvement in students’ vocabulary mastery after learning through Blooket Games. The experimental class showed a higher increase in the average post-test score compared to the control class that was taught using conventional teaching methods. Statistical analysis using the independent sample t-test indicated that the significance value was lower than 0.05, which means that the use of Blooket Games had a significant effect on students’ vocabulary mastery. Therefore, Blooket Games can be used as an effective game-based learning medium to increase students’ vocabulary mastery and to create a more engaging and interactive learning environment at the junior high school level.